2009
DOI: 10.1080/10715760802590400
|View full text |Cite
|
Sign up to set email alerts
|

Dose-related cytoprotective effect ofα-lipoic acid on hydrogen peroxide-induced oxidative stress to pancreatic beta cells

Abstract: alpha-Lipoic acid (alpha-LA), an antioxidant used for diabetic polyneuropathy, was reported to induce AMP-activated protein kinase activation and reductions in insulin secretion in pancreatic beta-cells at high concentrations (> or = 500 micromol/l). This study investigated whether alpha-LA has a protective role under oxidative stress in beta-cells and its effect is dose-related. In INS-1 cells treated with alpha-LA (150-1200 micromol/l) for 24 h, alpha-LA itself (> or = 300 micromol/l) induced apoptotic death… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
23
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 42 publications
4
23
0
Order By: Relevance
“…The dosage and duration of a-lipoic acid intravenous infusion are the standard regimen used in clinical practice for the treatment of diabetic polyneuropathy, which were also shown to have potential cytoprotective effects on bcells under oxidative stress. 13 In accordance with our previous studies, short-term CSIIbased intensive treatment was very effective on improving glycemic control, lipid profile, b-cell function, and insulin sensitivity, resulting in immediate good glycemic control freed of medication in a large proportion of patients. The near-normoglycemia rate at month 3 in the CSII alone group and those in combination with rosiglitazone, MET, or alipoic acid were 72.5%, 87.5%, 90%, and 75%, respectively.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The dosage and duration of a-lipoic acid intravenous infusion are the standard regimen used in clinical practice for the treatment of diabetic polyneuropathy, which were also shown to have potential cytoprotective effects on bcells under oxidative stress. 13 In accordance with our previous studies, short-term CSIIbased intensive treatment was very effective on improving glycemic control, lipid profile, b-cell function, and insulin sensitivity, resulting in immediate good glycemic control freed of medication in a large proportion of patients. The near-normoglycemia rate at month 3 in the CSII alone group and those in combination with rosiglitazone, MET, or alipoic acid were 72.5%, 87.5%, 90%, and 75%, respectively.…”
Section: Discussionsupporting
confidence: 61%
“…On the other hand, the rapid normalization of glucotoxicity and lipotoxity along with physical exercises to reduce weight per se in patients treated with short-term CSII might occur with a strong antioxidative effect that exceeded the impact of a-lipoic acid itself, the latter of which was used in a relatively short period with a small dose. Because oxidative stress is a complex process involving a great many elements that might interfere with its link to the etiology and development of diabetes, we are not intending to negate a-lipoic acid as a potent antioxidant, which has been proved valid in previous in vitro and in vivo studies for its effect on b-cell function and insulin sensitivity, 13,36,37 but the combination with a-lipoic acid might not be advantageous over CSII alone from a costeffectiveness point of view.…”
mentioning
confidence: 99%
“…Fifty mM H 2 O 2 was used as positive control to induce apoptosis. 17) At the end of treatment, cells were harvested by trypsin-EDTA digestion and resuspended in binding buffer (2 Â 10 5 cells/mL). Cells (195 mL) were incubated with 5 mL of Annexin V-FITC for 15 min at room temperature in the dark.…”
mentioning
confidence: 99%
“…It has been reported that oral administration of salbutamol, a beta 2 adrenergic agonist, can significantly reduce interleukin-12 and gamma interferon levels in patients with MS (Makhlouf et al, 2001). CAT can clear away the primary oxidation products such as H 2 O 2 , reducing their oxidative damage abilities (Tolman and Dalpiaz, 2007;Lee et al, 2009). Increased expression of CAT in the mitochondria is taken as evidence of improvement of mitochondrial anti-oxidative stress levels.…”
Section: Discussionmentioning
confidence: 99%